Analisis Du Pont System untuk Menilai Kinerja Keuangan PT Mayora Indah Tbk - Windi Ayuningtyas; Yesha Fatikah Sari; Kinanti Aulia; Noni Gloria Yataluan (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
This study aims to analyze the financial performance of PT Mayora Indah Tbk using the Du Pont System approach. This method decomposes Return on Equity (ROE) into three main components: Net Profit Margin (NPM), Total Asset Turnover (TATO), and Equity Multiplier (EM). The research employs secondary data from the company’s 2023 and 2024 financial statements. The findings reveal that despite an increase in net sales, the company experienced a decline in net profit, asset efficiency, and ROE. ROE decreased from 21.29% in 2023 to 17.84% in 2024, influenced by a reduction in NPM and TATO, along with a rise in EM. This decline indicates pressures on profitability and asset efficiency. Therefore, the company should enhance operational efficiency and manage its capital structure effectively to sustain optimal financial performance.